2012
DOI: 10.1097/aco.0b013e32834f6c4c
|View full text |Cite
|
Sign up to set email alerts
|

Can anaesthetic technique effect postoperative outcome?

Abstract: Further prospective, large-scale human trials with long-term follow-up are required to clarify the association between anaesthesia and cancer recurrence, neurotoxicity and the developing brain and long-term postoperative cognitive dysfunction in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 90 publications
1
31
0
Order By: Relevance
“…[9] In addition, the risk of POCD is increased, especially in elderly patients. [10] Intraoperative blood transfusion and liquids infusion has been found to influence body temperature regulation during surgery. [10] In recent years, constant temperature infusion mechines, which can warm the infusion temperature to the temperature of patients’ body, have been widely used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] In addition, the risk of POCD is increased, especially in elderly patients. [10] Intraoperative blood transfusion and liquids infusion has been found to influence body temperature regulation during surgery. [10] In recent years, constant temperature infusion mechines, which can warm the infusion temperature to the temperature of patients’ body, have been widely used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Intraoperative blood transfusion and liquids infusion has been found to influence body temperature regulation during surgery. [10] In recent years, constant temperature infusion mechines, which can warm the infusion temperature to the temperature of patients’ body, have been widely used in clinical practice. They have demonstrated an effective reduction of the incidence of adverse events caused by low temperature of infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that the anesthetic and/or analgesic approach used during surgery and the perioperative period may influence cancer recurrence [33, 34]. Certain perioperative anesthetics and analgesics have the potential to impact cancer outcomes [3538], [35].…”
Section: Factors Influencing Loco-regional and Distant Metastatic Dismentioning
confidence: 99%
“…Some data indicated that [1] the incidence of postoperative cognitive dysfunction (POCD) in over 60-year-old patients was 25.8% 1 week after the major noncardiac surgery and 9.9% after 3 months. Transfusion is one of the risk factors of POCD [2]. A lot of blood transfusion could cause the occurrence of intraoperative hypothermia, especially for the elderly patients.…”
Section: Introductionmentioning
confidence: 99%